Tranexamic acid blocks the thrombin-mediated delay of epidermal permeability barrier recovery induced by the cedar pollen allergen, Cry j1. Issue 1 (December 2018) - Nakanishi, S.; Kumamoto, J.; Denda, M.
Abstract We previously demonstrated that Cry j1, the major pollen allergen ofCryptomeria japonica (Japanese cedar), transiently increases protease activity and intracellular Ca2+ concentration in cultured human keratinocytes, and delays recovery after stratum corneum barrier disruption in human skinex vivo . Topical application of tranexamic acid or trypsin-type serine protease inhibitors accelerates barrier recovery. We hypothesized that tranexamic acid might prevent the transient protease activity increase and the barrier recovery delay induced by Cry j1. Here, we tested this hypothesis and examined the mechanism involved. In cultured human keratinocytes, knock-down of protease-activated receptor 1 (PAR-1) reduced the transient increase of calcium induced by Cry j1, whereas knock-down of PAR-2 did not. Knock-down of thrombin significantly reduced the transient increases of calcium concentration and protease activity. Tranexamic acid, soybean trypsin inhibitor, or bivalirudin (a thrombin inhibitor) also reduced the calcium elevation induced by Cry j1 and/or thrombin. Co-application of tranexamic acid or bivalirudin with Cry j1 to human skinex vivo blocked the delay of barrier recovery. These results suggest that thrombin and PAR-1 or PAR-1-like receptor might mediate the adverse effects of Cry j1 on human epidermal keratinocytes, and could open up a new strategy for treating inflammatory skin diseases.